Use of Customized Employment in State Vocational Rehabilitation Programs: A Retrospective Study 2017–2020. (April 2023) - Kim, Jaeyoung; Inge, Katherine; Keeton, Beth; Riesen, Tim; Castruita-Rios, Yazmin; Tansey, Timothy N.
The purpose of this study was to examine the outcomes of customized employment via an analysis using the U.S. Rehabilitation Services Administration Case Service Report (RSA-911) from Federal Fiscal Years of 2017 through 2020. The independent variables were demographics, barriers to employment, and types of state vocational rehabilitation agency (SVRA) services, and the dependent variables were competitive integrated employment status and weekly earnings at exit. Descriptive analyses, multiple logistic regression, and hierarchical multiple regression comprised data analysis. The study sample ( N = 2, 280) was 57.9% male and 42.1% female and had a mean age of 32.69 years ( SD = 12.83). Seventy-seven percent identified themselves as White and 46.7% had a cognitive disability. The results of this study indicated that consumers who have cognitive disability and cultural barriers; are migrant farmworkers and/or dependents; and receive job placement assistance, short-term job supports, maintenance services, benefits counseling, and supported employment are more likely to get competitive integrated employment at exit ( R 2 = .34). Multiple variables were found to be significantly related to weekly earnings at exit and explained 24% of the variance. Rehabilitation counselors should take into consideration the findings of this study to determine from which supports consumers may benefit to attain successful employment goals, particularly for customized employment.